Decolorization of reactive violet 5 dye in textile wastewater by electrocoagulation - Borislav N. Malinovic; Miomir G. Pavlovic (Journal of Electrochemical Science and Engineering, 2016)
The textile dyeing industry consumes large quantities of water and produces large volumes of wastewater from different steps in the dyeing and finishing processes. Wastewater from printing and dyeing units is often rich in color, containing residues of reactive dyes and chemicals, such as complex components. This study investigates the decolorization of synthetic dye wastewater containing textile dye Reactive Violet 5 (RV5) by electrocoagulation. A laboratory batch reactor was used to investigate the effect of various operating parameters using aluminium (Al), iron (Fe) and stainless steel (SS) anode. The effect of dye concentration, current density, supporting electrolyte, supporting electrolyte concentration, electrolysis duration, and material of anode of the systems were evaluated. Color removal efficiency was 22, 91.5 and 99.8 % in 15 minutes using Al, Fe and SS anode, respectively (j = 10 mA/cm2, cNaCl = 0.171 M).